Counterfeit cosmetics perception among Muslim government servants in Wisma Persekutuan Taiping, Perak - Abdullah Thani, Ayu Kamareenna; Rosely, Nurhidayah; Alias, Noor Rahmawati (Journal of Islamic, Social, Economics and Development, 2025)
The aim of this research is to ascertain whether a significant difference exists in the perceptions of Muslim consumers concerning counterfeit cosmetic products in Wisma Persekutuan Taiping, contingent upon their degree of religiosity and brand awareness. We used the basic random sample method to get 239 surveys from Muslim government workers living in Wisma Persekutuan Taiping. We then used SPSS software to look at the data. The study's findings revealed a significant association between brand consciousness and the perception of Muslim government personnel in Wisma Persekutuan Taiping concerning counterfeit cosmetics. Furthermore, the findings demonstrated that there is no significant association between religiosity and the attitudes of Muslim government personnel in Wisma Persekutuan Taiping towards counterfeit cosmetics. This study contributes to the current literature on Halal cosmetics research and provides important information to authorities on how Muslim consumers see fake cosmetic items. These findings can help regulators make the halal cosmetics business better regulated.